THE ROLE Of THE MICROBIOTA IN THE HUMAN BODY AND ITS IMPACT ON THE IMMUNE SYSTEM - Shakirova Gavkharkhan Nazirgulomovna; Xomidov Elyor Muzaffarovich (Web of Journals Publishing, 2025)
The role of the microbiota in the human body and its impact on the immune system has become a significant focus of scientific research in recent years. The microbiota, a complex ecosystem consisting primarily of bacteria, viruses, fungi, and other microorganisms, plays an essential role in various biological processes such as immune function, digestion, metabolism, and mental health.
Keywords: Microbiota, immune system, autoimmune diseases, neurological diseases, metabolic diseases, healthcare, microorganisms, bacteria, viruses, fungi, immunization.